APLIKASI PENJUALAN DAN PERSEDIAAN BARANG: Humblezing Store is one of the convection that produces a variety of clothing and men’s jackets. In producing goods company uses quality materials so that the products have high quality. Marketing system which runs today are using social media such as Facebook and Blackberry Messenger (BBM). This is done because most Indonesian people today prefer a company that offers the ease of sale. The method used in the development of information systems sales and inventory is an engineering prototype. The system design modeling tool is a structured approach using tools such flowchart document (flowmap), context diagram, DFD (Data Flow Diagram), data dictionary, normalization, table relationships, and ERD (Entity Relationship diagrams). The programming language used is PHP using MySQL database server. Results of this study were (1) With a system of sales and inventory information is the consumers can find out information about Humblezing Store online. (2) The information system of sales and inventory that is proposed can improve and will provide service to consumers. Consumers who want to make purchases do not have to come directly to the store, but can make purchases anywhere. - Maulana, Riyan; Hasti, Novrini (PETIR, 2015)
Humblezing Store is one of the convection that produces a variety of clothing and men’s jackets. In producing goods company uses quality materials so that the products have high quality. Marketing system which runs today are using social media such as Facebook and Blackberry Messenger (BBM). This is done because most Indonesian people today prefer a company that offers the ease of sale. The method used in the development of information systems sales and inventory is an engineering prototype. The system design modeling tool is a structured approach using tools such flowchart document (flowmap), context diagram, DFD (Data Flow Diagram), data dictionary, normalization, table relationships, and ERD (Entity Relationship diagrams). The programming language used is PHP using MySQL database server. Results of this study were (1) With a system of sales and inventory information is the consumers can find out information about Humblezing Store online. (2) The information system of sales and inventory that is proposed can improve and will provide service to consumers. Consumers who want to make purchases do not have to come directly to the store, but can make purchases anywhere.